The rise of self-assembled monolayers for fabricating electrochemical biosensors-an interfacial perspective - Gooding, J.; Darwish, Nadim (2012)
Electrochemical biosensors have witnessed a tremendous growth in nanotechnology and in depth characterisation over the last two decades. In particular, modification of surfaces with self-assembled monolayers (SAMs) has provided a molecular control of the interfaces, which has paved the way to fabricate improved biosensing devices. Here we focus on the important advances of using SAMs in enzyme electrodes and affinity biosensors such as for peptides, DNA and antibodies.